Studi Literatur: Penerapan Metode Hungaria dalam Penugasan Program Linier untuk Mengoptimalkan Alokasi Waktu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the application of the Hungarian method in solving assignment problems based on linear programming, particularly in optimizing work time allocation. Through a literature review of 15 research articles, it was found that the Hungarian method consistently proves effective in improving work efficiency, reducing time waste, and optimally matching resources with appropriate tasks. These studies reported reductions in work time ranging from 3 to 663 minutes after applying the method, depending on the complexity and context of each case. Additionally, integrating the Hungarian method with software tools such as POM-QM and LINGO further accelerates the optimization process. The findings indicate that the Hungarian method is a practical, flexible, and relevant mathematical approach across various sectors, supporting operational decision-making in an objective and efficient manner.